Insights into the Strain Rate on Microstructure Evolution of Carbide‐Free Bainitic Steel. Issue 10 (29th July 2022) - Zhou, Songbo; Zhou, Wen; Liao, Weijie; Hu, Chengyang; Hu, Feng; Wang, Kun; Dong, Hangyu; Wu, Kaiming
Abstract : The microstructural transformation behavior of carbide‐free bainitic steel at different strain rates is investigated using a combination of scanning electron microscopy, transmission electron microscopy, and electron backscatter diffraction. The results demonstrate that the stress–strain relationship of the steel exhibits a dependence on the strain rate, with the tensile strength increasing from 1441 MPa at a strain of 0.1 s −1 to 1537 MPa at 500 s −1, with the elongation of the sample increasing from 16.0% to 22.0% under these conditions. The increase in the strain rate raises the degree of local deformation with blocky martensite/retained austenite, exhibiting that different degrees of fragmentation and bainitic ferrite laths are observed to undergo torsional deformation. Through continuous dislocation absorption, the dislocation walls and dislocation tangles gradually develop into low‐angle subgrain boundaries, primarily located in regions with high kernel average misorientation values. After deformation at a strain rate of 0.1 s −1, the sample exhibits a Brass texture and demonstrates a combination of both Brass + Goss textures at a strain rate of 500 s −1 . Abstract : Herein, the evolution of selected microstructure features, dislocation, crystallographic orientation, misorientation, and texture under different strain rates is studied using carbide‐free bainitic steel. The increase in the strain rate raised the degree of local deformation, through continuous dislocation absorption and the dislocation tangles gradually developed into low angle subgrain boundaries, primarily located in regions with high kernel average misorientation values.